Nemozoma gymnosternalis sp. nov., a new anomalous species of Trogossitidae from Brazil - Kolibáč, Jiří (Zootaxa, 2014)
Nemozoma gymnosternalis sp. nov., a new member of the tribe Trogossitini (Trogossitidae) from southeastern Brazil is described. The species is distinct in its morphological characters, namely the shortened elytra, abdominal tergites enwound with projected folds of ventrites, and modified structure of extremely shortened ovipositor. Léveillé’s assignment of Airora quadrimaculatus Léveillé, 1894 to the genus Corticotomus Sharp, 1891 is confirmed. The systematics of brachelytric species of Nemozoma Latreille, 1804 is briefly discussed. The presence of two projecting cranial horns, a structure that occurs in several unrelated beetle groups with a similar biology, is also mentioned.